The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00253-012-4623-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal through different pathways in an aged refuse bioreactor treating mature landfill leachate

Abstract: In this study, an aged refuse bioreactor was constructed to remove nitrogen in a mature landfill leachate. The nitrogen removal efficiency and the microbial community composition in the bioreactor were investigated. The results showed that the aged refuse bioreactor removed more than 90 % of total nitrogen in the leachate under the nitrogen loading rate (NLR) of 0.74 g/kg (vs) day, and the total nitrogen removal rate decreased to 62.2 % when NLR increased up to 2.03 g/kg (vs) day. Quantitative polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…A recent study34 showed that the abundance of nitrifying bacteria typically represents less than 1% of the total bacterial population in activated sludge, although those microbes are extremely important for nitrogen removal. Denitrifiers, including the genera Acidovorax , Azospira , Bacillus , Dechloromonas , Desulfovibrio , Flavobacterium , Hyphomicrobium , Meganema , Rhizobium , Rhodobacter , Rhodoplanes , and Thiobacillus , play an important role in treating mature landfill leachate35 and wastewater36. For example, Dechloromonas oxidizes benzene using nitrate as an electron acceptor37.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study34 showed that the abundance of nitrifying bacteria typically represents less than 1% of the total bacterial population in activated sludge, although those microbes are extremely important for nitrogen removal. Denitrifiers, including the genera Acidovorax , Azospira , Bacillus , Dechloromonas , Desulfovibrio , Flavobacterium , Hyphomicrobium , Meganema , Rhizobium , Rhodobacter , Rhodoplanes , and Thiobacillus , play an important role in treating mature landfill leachate35 and wastewater36. For example, Dechloromonas oxidizes benzene using nitrate as an electron acceptor37.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this technique can provide wider and more complete information about microbial community structures than previous conventional molecular biology techniques. For these reasons, 454-pyrosequencing has gained interest in the study of complex microbial communities such as those of wastewater treatment environments (Hu et al, 2012;Xie et al, 2013). Despite the potential of 454-pyrosequencing, the use of this novel technique with anammox reactors is still scarce (Costa et al, 2014;Pereira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to nitrite, nitrate can also be reduced by both autotrophic and heterotrophic denitrifying bacteria. The experiments in Part 3 showed that degradable carbon content played a pivotal role, indicating that the main microorganisms responsible for denitrification are typically heterotrophs (Lee et al, 2002;Xie et al, 2013). Carbon source is insufficient in our experiments, however, the autotrophic denitrifiers could still offset the loss, where the aged (45 years old) landfill bioreactor still possessed 3.8 mg N/kgsoil capacity of denitrification (Jokela et al, 2002).…”
Section: Evaluation Of Nitrogen Removal Of Different Simulated Leachatesmentioning
confidence: 60%
“…Apart from that, emission surges fluctuate as a function of loading rates, soil properties (e.g. moisture content, pH value and texture) and leachate quality, particularly with respect to nitrogen speciation (Silva et al, 2008;Xie et al, 2013). In summary, the heterogeneity of waste composition and conflicting technical implications compound landfill management.…”
Section: Introductionmentioning
confidence: 96%